The regulatory role of the european central bank and the european sovereign debt crisis: consequences in portuguese companies financing - Teixeira, Sandra Isabel Martins (2018)
Taking into account the impact that the sovereign debt crisis reached within the European Union, the objective of this study was to examine what regulatory role for European Central Bank (ECB) plays and how it can contribute to the control of the sovereign debt Member States. In this sense, a comparative analysis of the role of the ECB and the Federal Reserve (FED) in response to the international financial crisis was made. In the second part of this work, we used an econometric model of multiple linear regressions to assess the influence that the sovereign debt crisis has had in lending to Portuguese companies.